Lições para a história das ciências no Brasil: Instituto Pasteur de São Paulo - Ribeiro, Maria Alice Rosa [UNESP] (Casa de Oswaldo Cruz, Fundação Oswaldo Cruz, 1996)
Este artigo pretende mostrar a importância e o papel do Instituto Pasteur de São Paulo (1903-16) no desenvolvimento da ciência microbiológica no Brasil e no surgimento da indústria farmacêutica de capital nacional.

The article highlights the role played by São Paulo's Pasteur Institute (1903-16) in the development of microbiological science in Brazil and in the emergence of a pharmaceutical industry owned by Brazilian capital.
Lessons for the history of science in Brazil: São Paulo's Pasteur Institute
Keywords: história das ciências; história econômica; saúde pública; indústria farmacêutica; São Paulo; Brasil; history of science; economic history; public health; pharmaceutical industry; São Paulo; Brazil/Brasil